2001
DOI: 10.1007/s001980170136
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Risk Factors for Hip Fractures in Thai Women

Abstract: Hip fractures are among the most important causes of ill health and death among elderly people. Several potentially modifiable risk factors have been reported. Most claimed physical activity as a promising, inexpensive preventive measure for hip fracture. However, knowledge about risk factors for hip fracture in Asian populations is very limited. We therefore conducted a case-control study to assess the relationships between physical activity and risk of hip fractures in Thai women. From 14 hospitals in Thaila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Analytical studies from low-and middleincome countries have shown that the risk factors for fall-related injuries among women are the same as in high-income countries, namely, low bone density; co-morbid conditions such as hypertension and diabetes; low levels of physical activity; poor cognitive function; poor perceived health status; poor vision; and alcohol consumption. 17,18 In our study more than two thirds of the deceased aged 45 years and above had co-morbidities, which constitute significant risk factors for fall-related injury among older adults in India and other settings. 8,18,19 Studies have also suggested that environmental factors such as building structure and socioeconomic factors such as the availability of electric lighting may contribute to falls to a greater extent in low-and middle-income countries.…”
Section: Mortality From Unintentional Falls In India Researchmentioning
confidence: 60%
“…Analytical studies from low-and middleincome countries have shown that the risk factors for fall-related injuries among women are the same as in high-income countries, namely, low bone density; co-morbid conditions such as hypertension and diabetes; low levels of physical activity; poor cognitive function; poor perceived health status; poor vision; and alcohol consumption. 17,18 In our study more than two thirds of the deceased aged 45 years and above had co-morbidities, which constitute significant risk factors for fall-related injury among older adults in India and other settings. 8,18,19 Studies have also suggested that environmental factors such as building structure and socioeconomic factors such as the availability of electric lighting may contribute to falls to a greater extent in low-and middle-income countries.…”
Section: Mortality From Unintentional Falls In India Researchmentioning
confidence: 60%
“…Interestingly, the results of some studies suggest that breast-feeding may reduce the risk of hip fractures in elderly women. These studies reported a dose–response relationship between the average duration of breast-feeding per child and the risk of hip fracture [2427]. Bearing in mind that the majority of our female patients had a history of breast-feeding (86.8%), protective effect of breast-feeding can partly explain the lower rate of hip fracture in our population.…”
Section: Discussionmentioning
confidence: 76%
“…It has been reported previously (Kay et al 1997) that subjects did not recognize their driving impairment after diphenhydramine use. This is rather worrisome, because epidemiological studies showed increased traffic accident risk (Kay and Quig 2001), work-related injury (Gilmore et al 1996;Fireman 1997) and hip fractures (Boonyaratevej et al 2001) after firstgeneration antihistamine use on a daily basis. The unawareness of performance impairment is unlikely to stimulate users of sedative antihistamines to travel by public transport, instead of driving their own car.…”
Section: Diphenhydraminementioning
confidence: 97%